Allegory of water and light: a pyrotechnic spectacle on the Rhine river in Düsseldorf in 1585 (Móin-Móin Magazine - Studies in the Art of Puppetry, 2026)
The "Julian Wedding" celebrations held in Düsseldorf in 1585 constituted an opportune occasion to spectacularly stage the assertion of power of a duchy in crisis — governed by the von Jülich-Kleve-Berg family — through symbols of authority aimed at strengthening relations with the Empire. In this context, the recourse to aesthetic models and masters linked to the Italian Renaissance reveals itself as a deliberate political strategy, supported by the use of encomiastic allegory. A precious source for the reconstitution of these events is the contemporary account by Theodor Gramineus (Dietrich Gras), practically ignored by historiography.
Keywords: court ceremony; encomiastic allegory; italian renaissance; pyrotechnics; stage machinery